Teaching Gender and Sex in Contemporary America - Haltinner, Kristin; Pilgeram, Ryanne; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book provides innovative pedagogy, theory, and strategies for college and university professors who seek effective methods and materials for teaching about gender and sex to today's students. It provides thoughtful reflections on the new struggles and opportunities instructors face in teaching gender and sex during what has been called the "post-feminist era." Building off its predecessor: Teaching Race and Anti-Racism in Contemporary America, this book offers complementary classroom exercises for teachers, that foster active and collaborative learning. Through reflecting on the gendered dimensions of the current political, economic, and cultural climate, as well as presenting novel lesson plans and classroom activities, Teaching Gender and Sex in Contemporary America is a valuable resource for educators.
Introduction: Patricia A. Adler and Peter Adler -- PART I. Reframing Gender -- Chapter 1: Sex & Gender in International Sports: Athletes and the Social Construction of Sex by Sumner McRa -- Chapter 2: The Mis-education of Lady Gaga: Confronting Essentialist Claims in the Sex and Gender Classroom by Andrea Miller -- Chapter 3: Performances of Pronouns: Using Feminist Post-Structuralism to Explore the Social Construction of Gender by Alison Happel-Parkins -- Chapter 4: Undoing Gender: Making the Invisible Visible by Lindsay Custer -- Chapter 5: Queering the Sociology of Gender by Kristin Haltinner/- Chapter 6: Make Us Whole!: Deconstructing Gender Narratives to Build Solidarity by Annie D. Jollymore -- Chapter 7: SGS: A Sensitizing Concept for Teaching Gender Diversity by Linda J. Henderson -- PART II. Intersecting with Systems of Power -- Chapter 8: Choosing to Abort, Alter, Adopt, or Accept: Teaching about Abortion in the Undergraduate Classroom by Elroi Windsor -- Chapter 9: Teaching about Gendered Violence Without Disempowering Women by Jocelyn A. Hollander -- Chapter 10: Silence, Violence, Safety and Respect: The Challenges of Teaching about Gender and Violence by Nikki McGary -- Chapter 11: Women and Work: Teaching the Pay Gap by Cynthia D. Anderson and Kelly Faust -- Chapter 12: Teaching Work and Gender in the 21stCentury by Erin K. Anderson -- Chapter 13: An Autoethnographic Mix Tape: Deconstructing Gender Identity Through Music that has Meaning to "us" by Anita Harker -- Chapter 14: Pulp Friction: How College Women Navigate Identity, Sexuality and Gender Conformity in Recent Mega-Hit Book Series by Suzan M. Walters and Michael Kimmel -- Chapter 15: Doing Critical Pedagogy in an Ironically Sexist World by Valerie Chepp and Lester Andrist -- Chapter 16: Coding the Crisis of Masculinity by Kyle Green and Madison Van Oort -- Part III: Creating Intentional Classroom Dynamics -- Chapter 17: From Protest to Praxis or Being Real in the Classroom by Charlotte A. Kunkel -- Chapter 18: They Don't Get It: The Promise and Problem of Using Student Resistance as a Pedagogical Tool by Courtney Caviness, Patti Giuffre, and Maria Wasley -- Chapter 19: Learning for a Change: Rage and the Promise of the Feminist Classroom by Deborah J. Cohan -- Chapter 20: Teaching Spaces of Possibility: Cultivating Safe, Relaxed, and Challenging Classrooms by Danielle Antoinette Hidalgo -- Chapter 21: Agency and Activism as Elements in a 'Pedagogy of Hope' Moving Beyond 'This Class is Depressing' by Maggie Rehm -- Part IV: Teaching About Gender and Sex in Broader Contexts -- Chapter 22: The Pedagogical Challenge of Teaching Privilege, Loss, and Disadvantage in Classrooms of Invisible Social Identities by Traci Craig -- Chapter 23: Critical Pedagogy: Disrupting Classroom Hegemony by Tre Wentling -- Chapter 24: Infusing Feminist Disability Studies in Our Teaching by Heather Albanesi, Abby Ferber, Andrea O'Reilly Herrera, Emily A. Nusbaum, and Linda Ware -- Chapter 25: Teaching Gender in Other Classrooms: a View from the Outside by Jyoti Grewal Chapter 26: On Teaching About Sex and Gender in Each and Every Political Science Course by Daniel Brian Andersen -- Chapter 27: Making the Invisible Visible: Shining a Light on Gender and Sexuality in Courses Primarily Focused on Other Topics by Kelsy Burke and Alexa Trumpy -- PART V:Conclusion -- Chapter 28: Conclusion by Kristin Haltinner -- Appendixes.
Keywords: Sociology